1992
DOI: 10.1111/j.1755-3768.1992.tb04880.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired dacryocystitis: Microbiology and conservative therapy

Abstract: The dacryocystitis in adults is mainly caused by postsaccal stenosis of the lacrimal ducts. The banking up of the lacrimal fluid leads to an accumulation of germs and following infection. This report describes the clinical and microbiological findings in a large consecutive series of patients that presented at the outpatient clinic of the 2nd Department of Ophthalmology of the University of Vienna with the signs of acute, chronic recurrent or chronic infections of the lacrimal system between 1983 and the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 13 publications
5
31
1
Order By: Relevance
“…(10) The most common organisms cultured in our study were Staphylococcus species, accounting for 63.15% of the isolates. This percentage compares fairly well with the results of Thicker and Buffam, (11) Huber-Spitzy et al, (12) As stated in the studies of Mahajan and Alexander et al, (1980), Micrococci are increasingly accepted as human pathogens in ocular infections (16). Our study reported 5 (6.5%) strains of Micrococci from the dacryocystitis cases both in the direct Gram stain from the sample and also isolation of Micrococci in culture.…”
Section: Resultssupporting
confidence: 80%
“…(10) The most common organisms cultured in our study were Staphylococcus species, accounting for 63.15% of the isolates. This percentage compares fairly well with the results of Thicker and Buffam, (11) Huber-Spitzy et al, (12) As stated in the studies of Mahajan and Alexander et al, (1980), Micrococci are increasingly accepted as human pathogens in ocular infections (16). Our study reported 5 (6.5%) strains of Micrococci from the dacryocystitis cases both in the direct Gram stain from the sample and also isolation of Micrococci in culture.…”
Section: Resultssupporting
confidence: 80%
“…Inflammation and fibrosis may also be secondary to coexisting infectious colonization within the lumen of the lacrimal system (Huber-Spitzy et al, 1992). In a study conducted by Coden et al (1993), culture of lacrimal sac contents or lacrimal sac biopsy revealed positive culture results in 52.5% cases in external DCR.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic antibiotics are known to prevent infection and are associated with a greater success rate of surgery (Huber-Spitzy et al, 1992). Hence these were prescribed in our patients also.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative and anaerobic organisms have been reported to be present in 20%-27% and 7%-16% of patients with dacryocystitis, respectively (11,17,21,22) , and the incidence of these infections appears to be rising (10) . Gram-negative bacteria, including Pseudomonas aeruginosa, Enterobacter, Citrobacter spp., Haemophilus influenzae, and Escherichia coli, have also been reported as causative agents of dacryocystitis (10) .…”
Section: Discussionmentioning
confidence: 99%